Gut Dysbiosis in Chagas Disease. A Possible Link to the Pathogenesis - de Souza-Basqueira, Marcela; Ribeiro, Roberto Marques; de Oliveira, Léa Campos; Moreira, Carlos Henrique Valente; Martins, Roberta Cristina Ruedas; Franco, Diego Castillo; Amado, Pâmela Pontes Penas; Mayer, Marcia Pinto Alves; Sabino, Ester Cerdeira (Frontiers in Cellular and Infection Microbiology, 2020)
Chagas disease is caused by the flagellate protozoan Trypanosoma cruzi. Cardiomyopathy and damage to gastrointestinal tissue are the main disease manifestations. There are data suggesting that the immune response to T. cruzi depends on the intestinal microbiota. We hypothesized that Chagas disease is associated with an altered gut microbiome and that these changes are related to the disease phenotype. The stool microbiome from 104 individuals, 73 with Chagas disease (30 with the cardiac, 11 with the digestive, and 32 with the indeterminate form), and 31 healthy controls was characterized using 16S rRNA amplification and sequencing. The QIIME (Quantitative Insights Into Microbial Ecology) platform was used to analyze the data. Alpha and beta diversity indexes did not indicate differences between the groups. However, the relative abundance of Verrucomicrobia, represented primarily by the genus Akkermansia, was significantly lower in the Chagas disease groups, especially the cardiac group, compared to the controls. Furthermore, differences in the relative abundances of Alistipes, Bilophila, and Dialister were observed between the groups. We conclude that T. cruzi infection results in changes in the gut microbiome that may play a role in the myocardial and intestinal inflammation seen in Chagas disease.